2020
DOI: 10.1371/journal.pntd.0008205
|View full text |Cite
|
Sign up to set email alerts
|

Use of pyriproxyfen in control of Aedes mosquitoes: A systematic review

Abstract: Background Dengue is the most rapidly spreading arboviral disease in the world. The current lack of fully protective vaccines and clinical therapeutics creates an urgent need to identify more effective means of controlling Aedes mosquitos, principally Aedes aegypti, as the main vector of dengue. Pyriproxyfen (PPF) is an increasingly used hormone analogue that prevents juvenile Aedes mosquitoes from becoming adults and being incapable of transmitting dengue. The objectives of the review were to (1) Determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…This principle was the cornerstone of many of the earliest vector control strategies, where breeding sites were eliminated or diminished, or treated with larvicides to reduce the number of vectors in a population. It is also the rationale behind more contemporary strategies such as the dissemination of insect growth regulators like pyriproxyfen [ 57 ] or the release of Wolbachia -infected male mosquitoes [ 58 , 59 ]. Gut-associated microbes can influence vector density through the modulation of development, reproductive outputs, and resistance to abiotic stress.…”
Section: Influence Of Microbiota On Vector Density (M)mentioning
confidence: 99%
“…This principle was the cornerstone of many of the earliest vector control strategies, where breeding sites were eliminated or diminished, or treated with larvicides to reduce the number of vectors in a population. It is also the rationale behind more contemporary strategies such as the dissemination of insect growth regulators like pyriproxyfen [ 57 ] or the release of Wolbachia -infected male mosquitoes [ 58 , 59 ]. Gut-associated microbes can influence vector density through the modulation of development, reproductive outputs, and resistance to abiotic stress.…”
Section: Influence Of Microbiota On Vector Density (M)mentioning
confidence: 99%
“…aegypti in the LRGV. Pyriproxyfen is an insect growth regulator that targets immature stages of mosquitoes; it acts at very low doses and it persists for several months in larval habitats [ 20 , 21 ]. Therefore, autodissemination stations that rely on pyriproxyfen might have a meaningful impact as a control tool in areas were source reduction campaigns are unfeasible or cost prohibitive [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…23,[29][30][31] The use of JHA pyriproxyfen for controlling Aedes mosquitoes has increased dramatically during the past few years, 32,33) a recent review summarizes these applications. 34)…”
Section: Jha Application Kills Pupae But Not Larvae In Some Insectsmentioning
confidence: 99%
“…Methoprene is the most widely used JHA for controlling mosquito larvae. 22,23,[29][30][31][35][36][37][38][39][40][41][42][43][44][45] However, recent studies showed the efficacy of pyriproxyfen for larval control and adult sterilization of various mosquito species, 24,28,[32][33][34] which might increase the use of this chemical for vector control. In contrast, hydroprene was not used much for mosquito control.…”
Section: Jha Efficacy Is Variable Among Insect Pests and Disease Vectors Testedmentioning
confidence: 99%